Psychometric properties: Assertiveness scale in peruvian schoolchildren - Rosario Quiroz, Fernando Joel (2020)
The purpose of this research was to determine the psychometric properties of the ADCA 1 assertiveness scale, the type of research is instrumental; we worked with a sample of 730 individuals between the ages of 13 and 16. It was considered a non-probabilistic sample by trials. The results indicate that the Self-Assertiveness scale in its original proposal does not present evidence of construct validity (X2 / gl = 2,648; GFI = 0.883; CFI = 0.807; RMSEA = 0.048 and SRMR = 0.0532); After analyzing the items, an exploratory analysis with an oblique rotation is sought, obtaining 5 factors that explain 43,602% of the construct. The adjustment index of the 5-factor proposal presents evidence of construct validity (X2 / gl = 2,225; GFI = 0.936; CFI = 0.900; RMSEA = 0.041; SRMR = 0.0463), a general level the scale with 25 items presents a αordinal = 0.902 and u Ω = 0.902. In conclusion, the 25-item proposal presents evidence of reliability and validity.